An electrochemical method for determination of amaranth in drinks using functionalized graphene oxide/chitosan/ionic liquid nanocomposite supported nanoporous gold. (15th January 2022) - Zhang, Qiaoyun; Cheng, Weiwei; Wu, Di; Yang, Yuling; Feng, Xiao; Gao, Chengcheng; Meng, Linghan; Shen, Xinchun; Zhang, Yan; Tang, Xiaozhi
Graphical abstract: Highlights: Functionalized graphene-oxide (fGO) were modified with chitosan (CS) and Ionic liquid (IL). An electrochemical sensor coated with nanoporous gold (NPG) and fGO/CS/IL was fabricated. The fGO/CS/IL/NPG/GCE showed the highest redox peak current response signal of Amaranth. The detection range of fGO/CS/IL/NPG/GCE for Amaranth was from 8 to 1200 nM. The sensor was applied for Amaranth detection in commercial drinks with satisfactory results. Abstract: An electrochemical sensor was fabricated by modifying nanoporous gold (NPG)-coated glassy carbon electrode (NPG/GCE) with functionalized graphene oxide /chitosan/ionic liquid nanocomposites (fGO/CS/IL). The introduction of ionic liquid (IL) and chitosan (CS) induced higher dispersibility of functionalized graphene oxide (fGO), and was beneficial for the combination of fGO/CS/IL with NPG/GCE. As a result of the synergistic effect of NPG and fGO/CS/IL, the resulted functionalized graphene oxide/chitosan/ionic liquid nanocomposites/nanoporous gold /glassy carbon electrode (fGO/CS/IL/NPG/GCE) showed the highest redox peak current response signal of Amaranth (E123) due to ultrahigh surface area, electronic conductivity as well as the improvement of the surface structure. Under optimized conditions, the enhanced peak currents represented excellent analytical performance for detection of Amaranth in the concentration range from 8.0 to 1200.0 nM. Meanwhile, the fGO/CS/IL/NPG/GCE presented satisfactory sensitivity and selectivity, excellent reproducibility, and long-time stability. For practical applications, the fGO/CS/IL/NPG/GCE was validated for the determination of Amaranth in three types of drinks with satisfactory results.